Obesity and COVID-19 in-hospital fatality in southern Brazil: impact by age and skin color - Houvèssou, Gbènankpon Mathias; Leventhal, Daniel G P; Silva, Eduardo Viegas da (Revista de Saúde Pública, 2022)
OBJECTIVES: To estimate the relative risk (RR) of death associated with obesity, the attributable fraction in the exposed/with obesity (AFo), and the hospitalized population attributable risk (hospitalized PAR) associated with obesity of death among all adults and among Black and non-Black adults hospitalized for severe COVID-19 in the state of Rio Grande do Sul, Brazil. METHODS: This retrospective cohort study of prognostic factors analyzed all cases of adults hospitalized for severe COVID-19 in the state of Rio Grande do Sul, Brazil. The occurrence of obesity by hospital teams was primarily measured observing individuals’ medical records. The outcome assessed was hospital deaths caused by severe COVID-19. Poisson regression was used to estimate RRs and 95% confidence intervals (95%CI). RESULTS: The study sample consisted of 100,099 patients hospitalized for severe COVID-19, most of whom were White (84.7%) and male (54.7%). The effect of obesity was strongly modified by age. For the 18–39-year-old age group, RR = 2.54 (95%CI: 2.33–2.77), and in individuals 70 years and above, RR = 1.09 (95%CI: 1.05–1.13). For the 18–39-year-old age range, AFo = 60.6% and AFo = 42.5% in individuals 40–59 years old. For all hospitalizations, the hospitalized population attributable risk (hospitalized PAR) measuring obesity for individuals 18–39 years old was 25.3%, while in the 40–59-year-old range, the hospitalized PAR = 11.2%. The hospitalized PAR was 31.7% in the Black population aged 18–39 years and 24.8% in non-Blacks. The hospitalized PAR was also larger in Blacks aged 40-59 years. CONCLUSIONS: Obesity largely impacted in-hospital case-fatality rates among young adults and Black people contaminated by COVID-19. These data highlight the extent of the risk concerning obesity, a highly prevalent chronic condition.